Bibliometric Analysis of Thematic Trends in Research in Law, Communication and Social Sciences: Implications for the Editorial Approach - Agustín Vicedo; Mario A. García; Eugenio R. Borroto (PT. Riset Press International, 2026)
This paper explores emerging trends in interdisciplinary research that connect Law, Communication, and Society, considering an editorial approach focused on high-impact scientific publications. A systematic review of recent literature (last five years) is presented, identifying key thematic areas (digital governance, democratic discourse, digital rights, media literacy, media justice) that cut across the three fields. Furthermore, a bibliometric analysis of relevant publications reveals a growth in research on digital regulatory artifacts and algorithmic justice, as well as a concern for public discourse and information inequality. Thirty leading journals (10 in Law, 10 in Communication, and 10 in Social Sciences) were selected according to SCImago 2024, and their editorial profiles were analyzed. Finally, each main theme is aligned with SDGs 16, 10, 5, and 4, showing direct links (e.g., democratic transparency—SDG 16, gender equality in the media—SDG 5), and emerging gaps are highlighted (algorithmic justice, democratic backsliding in the Global South, disinformation in legal processes). These findings support the proposal for an interdisciplinary publication aimed at strengthening rights and social participation in the digital age. This study contributes a structured editorial framework integrating bibliometric mapping, thematic clustering, and SDG alignment to consolidate the interdisciplinary field of Law, Communication, and Society. By identifying critical gaps (algorithmic justice, democratic backsliding in the Global South, and disinformation in judicial contexts), it offers a strategic roadmap for academic journals. Moreover, it provides actionable insights for editorial management, prioritizing socially urgent yet underfunded themes such as digital gender violence, media literacy policies, and algorithmic accountability, thereby advancing a coherent and globally relevant research agenda.